Kicking velocity and effect on match performance when using a smaller, lighter Ball in women`s football - Andersen, T. B.; Krustrup, P.; Bendiksen, M.; Orntoft, C. O.; Randers, M. B.; Pettersen, S. A. (International Journal of Sports Medicine, 2016)
The present study evaluated the effect of a smaller, lighter ball on kicking speed and technical-tactical and physical match performance in high-level adult female footballers. In the laboratory test setting, the peak ball velocity was 6% higher with the new ball (NB) than the standard ball (SB) (26.5±0.5 vs. 25.1±0.5 m·s-1, p<0.05). However, during match-play, no differences were observed in mean heart rate (87±5 vs. 87±5%HRmax; p>0.05), blood lactate (90 min: 4.7±1.7 and 4.0±1.7 mmol·l-1; p>0.05), total distance covered (10.6±0.9 and 10.4±0.8 km; p>0.05), intense running (>16 km/h) (2.08±0.42 and 1.94±0.38 km; p>0.05) and match-induced decrement in Yo-Yo IR1 performance (28 vs. 31%, respectively, p<0.05) using NB compared to SB. Likewise, no difference was observed in the number of short, medium-range or long passes during matches played with the 2 ball types, and there was no difference in passing success rate (NB: 68±1% and SB: 68±1%, p>0.05). In conclusion, high-level adult female footballers had a higher kicking speed when using a smaller, lighter ball, but no differences were observed during match-play with the 2 ball types in respect of technical-tactical and physical match performance. The physical loading was high for the players when playing with both ball types.